Circadian Clock Gene Bmal1: A Molecular Bridge from AKI to CKD - Songyuan Yang; Zehua Ye; Lijia Chen; Xiangjun Zhou; Wei Li; Fan Cheng (Biomolecules)
Acute kidney injury (AKI) and chronic kidney disease (CKD) represent two frequently observed clinical conditions. AKI is characterized by an abrupt decrease in glomerular filtration rate (GFR), generally associated with elevated serum creatinine (sCr), blood urea nitrogen (BUN), and electrolyte imbalances. This condition usually persists for approximately a week, causing a transient reduction in kidney function. If these abnormalities continue beyond 90 days, the condition is redefined as chronic kidney disease (CKD) or may advance to end-stage renal disease (ESRD). Recent research increasingly indicates that maladaptive repair mechanisms after AKI significantly contribute to the development of CKD. Thus, implementing early interventions to halt the progression from AKI to CKD has the potential to markedly improve patient outcomes. Although considerable research has been conducted, the exact mechanisms linking AKI to CKD are complex, and effective treatments remain limited. Kidney function is influenced by circadian rhythms, with the circadian gene Bmal1 being vital in managing these cycles. Recent research indicates that Bmal1 is significantly involved in the progression of both AKI and CKD. In this study, we conducted a retrospective analysis of Bmal1’s role in AKI and CKD, reviewed recent research advancements, and investigated how Bmal1 influences the pathological mechanisms underlying the progression from AKI to CKD. Additionally, we highlighted gaps in the existing research and examined the potential of Bmal1 as a therapeutic target in kidney disease management. This work aims to provide meaningful insights for future studies on the role of the circadian gene Bmal1 in the transition from AKI to CKD, with the goal of identifying therapeutic approaches to mitigate kidney disease progression.